Studi Pendahuluan Preliminary Study on Students Critical Thinking Skills on Temperature and Heat Material - Irvan Nur Rizki; Leni Marlina; Ismet Ismet (Postgraduate, University of Mataram, 2024)
This preliminary study investigates the critical thinking skills of Grade VII students at SMP Negeri 01 Belitang Jaya on the topic of temperature and heat, focusing on Ennis's critical thinking indicators. It aims to identify students' critical thinking levels based on five indicators and highlight areas needing improvement. The study uses a qualitative descriptive method, involving 154 students from five classes. Data were collected through questionnaires covering five indicators: providing simple explanations, building basic skills, drawing conclusions, providing further explanations, and managing strategies and tactics. The findings show that students excel in providing simple explanations (74.66%, high category). However, they perform moderately in building basic skills (46.79%), drawing conclusions (58.54%), and providing further explanations (41.60%). Managing strategies and tactics scored the lowest (31.20%, low category). These results suggest a need for targeted educational interventions, especially in strategy and tactics management. The study provides a reference for developing interactive teaching materials, such as augmented reality-assisted e-modules, to improve students' engagement and critical thinking skills. It lays the groundwork for innovative teaching strategies to make the learning process more effective and engaging